The roles of arbuscular mycorrhizal fungi in the intensity of the foot rot disease on pepper plant from the infected soil - Norma Fauziyah; Bambang Hadisutrisno; S Suryanti (Brawijaya University, 2017)
Pepper (Piper nigrum L.) is an important spice plant of Indonesia. In Bangka Belitung Province, the main pepper producer, pepper has been the most commonly cultivated commodity. However, the production has declined from time to time. One of the causes of the decline is Pepper Fot Rot, caused by Phytophthora capsici. The rapid spread and development of the disease is mainly due to utilization of diseased plant materials for pepper cuttings and infested or diseased plantation soil. The materials used in this research included the infected soil taken from the infectedpepper plantation at Bangka Island with disease intensity of pepper foot rot 60%, inoculum of Arbuscular Mycorrhizal fungi in the zeolite medium, compost, and pepper seedling from Natar variety. This research was done by planting pepper seedling on infected soil and observing plant height, disease intensity, and infection of AM fungi on the roots. The results showed that soil from diseased pepper plants harbored high population of plant pathogens inoculum and caused the death of 9 week-old cuttings and retarded growth of the survivors. Sterilization of the infected soil with hot water vapor for 3 hours still could not control the pathogen. Good growth was observed on one node cutting planted in sterile soil amended with arbuscular mycorrhizal fungi.